Friction Stir Welding of Magnesium Alloys: A Review - Singh, Kulwant; Singh, Gurbhinder; Singh, Harmeet (Asian Review of Mechanical Engineering, 2016)
The Increasing global demands for energy conservation and environmental protection have encouraged manufacturers to develop lightweight components. Magnesium alloys are characterized by unique properties and offer opportunities for lightweight applications. There is a challenge to join the materials with a variety of applications along with cheaper value and high strength to weight ratio. Friction stir welding (FSW) is a solid state joining process used for light weight alloys. In this article, the recent developments of the FSW of magnesium alloys are reviewed to assist researchers to develop an in-depth understanding of the current state of the Friction Stir Welding of Magnesium Alloys.